The Role of Community Service Through Real Work Lectures (KKN) in Kota Raya Darat Village, Lahat Regency - Utama, Muhamad Risqi; Sari, Yolanda; Tulhuiriah, Ulfa; Sari, Nadela Permata; Marsela, Lara; Maulana, Muhammad Ikhwan; Mareta, Nanda; Agustina, Mike Nia; Dessyka, Dessyka; Fatmasari, Desi; Yelia, Yelia; Dewi, Dismita Citra (Indonesia Berdaya, 2025)
Community service through Real Work Lectures (KKN) is a form of student contribution to overcoming problems in the community. This study aims to examine the role of KKN in increasing environmental awareness and providing education to children in Kota Raya Darat Village, Lahat Regency. The method used in this study is observation. KKN students participate in ecological cleaning activities, counseling on overcoming juvenile delinquency, and educating children about caring for themselves. The study results show that through KKN, environmental awareness in Kota Raya Darat Village has increased significantly. People are beginning to understand how important it is to maintain cleanliness and take care of their surrounding environment. Children also show increased knowledge about the importance of protecting the environment through educational activities carried out by students.